Cell Wall Pectin and its Methyl-esterification in Transition Zone Determine Al Resistance in Cultivars of Pea (Pisum sativum) - Li, Xuewen; Li, Yalin; Qu, Mei; Xiao, Hongdong; Feng, Yingming; Liu, Jiayou; Wu, Lishu; Yu, Min (Frontiers in Plant Science, 2016)
The initial response of plants to aluminum (Al) is the inhibition of root elongation, while the transition zone is the most Al sensitive zone in the root apex, which may sense the presence of Al and regulate the responses of root to Al toxicity. In the present study, the effect of Al treatment (30 μM, 24 h) on root growth, Al accumulation, and properties of cell wall of two pea (Pisum sativum L.) cultivars, cv Onward (Al-resistant) and cv Sima (Al-sensitive), were studied to disclose whether the response of root transition zone to Al toxicity determines Al resistance in pea cultivars. The lower relative root elongation (RRE) and higher Al content were founded in cv Sima compared with cv Onward, which were related to Al-induced the increase of pectin in root segments of both cultivars. The increase of pectin is more prominent in Al-sensitive cultivar than in Al-resistant cultivar. Aluminum toxicity also induced the increase of pectin methylesterases (PME), which is 2.2 times in root transition zone in Al-sensitive cv Sima to that of Al resistant cv Onward, thus led to higher demethylesterified pectin content in root transition zone of Al-sensitive cv Sima. The higher demethylesterified pectin content in root transition zone resulted in more Al accumulation in the cell wall and cytosol in Al-sensitive cv Sima. Our results provide evidence that the increase of pectin content and PME activity under Al toxicity cooperates to determine Al sensitivity in root transition zone that confers Al resistance in cultivars of pea (Pisum sativum).